Intestinal Malrotation in Children: Experience of a Tertiary Care Hospital in a Developing Country - Emeka, Chukwubuike Kevin (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Intestinal malrotation is a congenital disorder resulting from abnormal rotation of the intestine during fetal development. The aim of this study was to evaluate our experience in the management of pediatric patients with intestinal malrotation. Material and Methods: This was a retrospective study of children aged 3 years and below who were treated for intestinal malrotation between January 2014 and December 2018 at the pediatric surgery unit of Enugu State University Teaching Hospital (ESUTH) Enugu, Nigeria. Results: Sixty-one patients had laparotomy for intestinal malrotation during the study period. There was predominance of male neonates and the age range was 10 days to 3 years. Abdominal pain and upper gastrointestinal tract contrast study were the most common symptom and investigation respectively. Intestinal obstruction caused by congenital (Ladd’s) bands was the most common intraoperative finding and Ladd’s procedure was the most performed surgical procedure. Most patients did not develop any post-operative complications. However, surgical site infection was the most common complication following surgery. Mortality occurred in 8 (13.1%) patients. Conclusion: Intestinal malrotation symptoms occur mainly in male neonates and abdominal pain is a common and consistent symptom. Upper gastrointestinal contrast study is diagnostic. There are morbidity and mortality associated with treatment of intestinal malrotation.